PENGARUH LATIHAN PASSING BAWAH BERPASANGAN TERHADAP KETERAMPILAN PASSING BAWAH PADA TIM BOLA VOLI PUTRA SMA NEGERI 1 KAMPAR TIMUR - Rusman Alwi; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the observations that the author did on the field on the volleyball team of male Kampar Timur 1 High School, the under-passing skills were not so good. This can be seen from several matches that have been followed such as in competitions between levels of schools in Kampar District even in Pekanbaru. The men's volleyball team at Kampar Timur 1 High School at the time of under-passing was not so optimal, such as: 1. passing did not reach friends, 2. the ball did not go up when making a lower pass, 3. The movement was not perfect when doing bottom passing. This study aims to find out: The effect of under-passing training paired up against the passing skills under the volleyball athlete Putra Kampar Timur 1 High School. The population in this study was the Putra Middle School volleyball team who participated in volleyball practice in Kampar Timur 1 Public High School, totaling 12 people. The sample uses total sampling technique so that the sample is 12 people. The instrument in this study was a low passing skill. Data obtained was analyzed by t test. Based on the data analysis and discussion, it can be concluded that there is an exercise effect Passing down on the lower passing skills of the male volleyball team in Kampar Timur 1 Public High School proved by the results of t count 4.024> t table 1.796 at α = 0.05.Key Words; Lower Passing Exercise, Lower Passing Skills